THE FREQUENCY OF OLD WORLD CUTANEOUS LEISHMANIASIS IN SKIN ULCERS IN PESHAWAR - Rahman, Saeedur; Abdullah, Fatima Humera; Khan, Jamshaid Ali (Journal of Ayub Medical College Abbottabad, 2009)
Background: Old World Cutaneous Leishmaniasis (OWCL) is a preventable skin infection that leads to morbidity and social isolation. It is spreading rapidly. The sore of OWCL may be a non-ulcerative red papule, nodule or a large mutilating ulcer. The ulcer is typically painless and can leave a disfiguring scar. Methods: This was a descriptive study. The diagnosis of OWCL was established by finding LD bodies in skin smear preparation. Results: This study identified 1680 cutaneous leishmaniasis in 1767 skin ulcers. Children (n=924) were infected more than other age groups (n=756). There were typical skin sore of OWCL in 1512 cases while 168 patients had atypical presentation. The ulcers were painless in 1603 patients. History of insect bite was present in 1366 cases, thorn prick in 156 patients, religious visit to endemic areas in 256 patients, and 4 patients had post surgical non healing wound. Lesions with 4 to 6 months of age had a maximum yield of LD bodies. There were 498 patients from different areas of Peshawar; 688 cases from leishmania endemic belt of FATA while 89 patients came from other urban and rural areas of NWFP. Conclusions: There is a tremendous increase in cases of OWCL and the disease became endemic in many regions of Pakistan. The bordering areas along Afghanistan have constituted an endemic belt that had invaded the neighboring urban and rural areas. Several chronic non healing ulcers had been diagnosed as OWCL. Many cases have been detected in Peshawar. People need education about the nature of the diseases and the efficacy of personal protective measures. Spray with suitable insecticides is required in all residential areas. Keywords: Leishmaniasis, sand flies, amastigote, non-healing ulcers, disfiguring scar